Explosive tumor growth in a patient with colon cancer is associated with reduced neoantigen levels and decreased interferon-gamma (IFN-γ) signaling - Yaqi Wang; Jiahua Lu; Dandan Huang; Pengju Chen; Jingyi Shi; Jie Cheng; Jingbo Gan; Ruifeng Li; Jingxuan Xu; Zhaoya Gao; Xiaodong Wang; Wensheng Huang; et al. (BMC Cancer)
Abstract Background Explosive tumor growth is characterized by rapid tumor growth in a short time period. Currently, there is no precise scientific definition for the condition, which is often accompanied with a poor clinical prognosis. Herein, we presented a study of a young patient with colon cancer who experienced explosive tumor growth. A clinical multidisciplinary team (MDT) collaborated with bioinformaticians to provide precise treatment and elucidate the biological mechanisms underpinning this growth. Methods A 28-year-old male patient diagnosed with colon cancer experienced explosive tumor growth. Peripheral bloods (PB) during immunotherapy were collected for immune cytokine analyses and flow cytometry assays on immune cell subsets. To further examine the underlying mechanisms of this explosive-growth, we conducted whole exome sequencing (WES) and RNA-sequencing (RNA-seq) of samples taken at different time points. Results The patient was diagnosed with Lynch syndrome. We implemented an immunotherapy and performed PB immune cytokine assays before, during, and after this therapy. Our observations suggested that immunotherapy may remodel interferon-gamma (IFN-γ) signaling and enhance T cell-mediated immune responses. By exploring explosive tumor growth mechanisms, we observed that tumors had significantly less insertion and deletion (INDEL) mutations and INDEL-derived neoantigens. Additionally, they had deficient antigen presentation functions as characterized by decreased IFN-γ signaling activity. Conclusions Neoantigen loss and decreased IFN-γ signaling activity contributed to explosive tumor growth in this patient. Recovered IFN-γ signaling may lead to effective immunotherapy outcomes.